Primary mediastinal paraganglioma associated with a familial variant in the succinate dehydrogenase B subunit gene. Issue 2 (10th September 2017) - Samuel, Nardin; Ejaz, Resham; Silver, Josh; Ezzat, Shereen; Cusimano, Robert J.; Kim, Raymond H.
Abstract : Surgical management is the mainstay of therapy for primary cardiac tumors, yet due to the rarity of these malignancies, their management and workup remains a challenge. Here, we report a unique case of a patient with a primary left ventricular cardiac paraganglioma (PGL) and describe the role of a medical genetics assessment leading to the identification of a rare variant in the SDHB gene to be the causative etiology of this cardiac tumor. Due to decreasing costs and accessibility of molecular genetic analysis, genetic testing may become an emerging diagnostic adjunct in cases of cardiac tumors.